# check!

posted by
**ben!** on
.

Write a recursive formula that generates the terms of the following:

. . .1, 3, 9, 27

my answer:

t1=1, n>2 --> tn= 3tn-1

is this correct?

Let's test

You have the sequence 1, 3, 9, 27 ...

You wrote

t_{1}=1, n>2 => t_{n}= 3t_{n}-1

What is t_{2}? It's undefined so I don't know how to continue.

I think you're supposed to observe that the sequence is powers of 3

1=3^{0}, 3^{1}, 3^{2}, 3^{3}, ...

Let t_{1}=1 and t_{n}=3t_{n-1}

Try that and see if it works.